Feasibility and utilisation of improved vegetable production technologies in family farming by agricultural labourers in the Thrissur district - Abdul Jabbar P K (Department of Agricultural Extension, College of Horticulture, 1996)
The research study entitled “Feasibility and Utilization of Improved Vegetable Production Technologies in family farming by agricultural labourers in the Thrissur district” was conducted to analyse the feasibility and utilization of vegetable production technologies in family farming by the agricultural labourers in Thrissur district in relation to their personal and socio-economic factors and to assess the constraints and consequences these of. The study area comprised of five panchayats namely, Pananchery, Puthur, Nadathara, Mattathur and Thekkumkara and a total of 100 agricultural labourers engaged in family farming were selected as respondents. Data were collected from the agricultural labourers using a pre-tested structured interview schedule. Appropriate statistical techniques like correlation analysis, regression analysis and path analysis were done to analyse the data. The perception of feasibility of technologies and extent of utilization were measured using arbitrary scale developed for the purpose. Five crops namely, brinjal, bittergourd, pumpkin, ladies finger and amaranthus were selected for the study with five selected practices under each crop. The study revealed that amaranthus received the highest feasibility score, while bittergourd and brinjal received feasibility perception scores below the average feasibility score. Foliar fertilization in amaranthus received the highest feasibility perception score. Among crop varieties, pumpkin varieties were the most preferred while bittergourd varieties got the least scores. Majority of agricultural labourers belonged to the medium category in extent of utilization and only 19 per cent were low adopters. Amaranthus production technologies received the highest utilization score while bittergourd received the lowest. Split application of fertilizer received the high utilization index in brinjal and bittergourd cultivation. The correlation analysis revealed that all independent variables except experience in vegetable cultivation were positively correlated with feasibility perception. Variables like farm size, annual income, innovativeness, economic motivation, management orientation and knowledge were significant in influencing the feasibility perception. All variables except experience in vegetable cultivation were found positively correlated with utilization of IVPT. Knowledge on IVPT exerted the largest direct effect. Information seeking behaviour, FFT-Actual, social participation and attitude towards scientific agriculture, management orientation, area under vegetables and extension orientation were found to influence significantly. Plant protection was cited to be the most preferred area where training was required, followed by improved varieties of crops harvesting and post harvest aspects and manures and fertilizers respectively. Constraints such as uneconomic holding size, inadequacy of capital, increased cost of plant protection chemicals and lack of leisure time, availability were cited as most important.Economic utilization of leisure time, enhancement of family income, generation of additional employment and promotion of family integrity were the important consequences. Lack of time to care children and other house operations and drudgery were cited to be the negative consequences.